2003
DOI: 10.1128/aem.69.11.6447-6454.2003
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Ammonium Oxidation Measured in Sediments along the Thames Estuary, United Kingdom

Abstract: Until recently, denitrification was thought to be the only significant pathway for N 2 formation and, in turn, the removal of nitrogen in aquatic sediments. The discovery of anaerobic ammonium oxidation in the laboratory suggested that alternative metabolisms might be present in the environment. By using a combination of 15 ؊ . We observed a shift in the significance of anaerobic ammonium oxidation to N 2 formation relative to denitrification, from 8% near the head of the estuary to less than 1% at the coast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
252
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(272 citation statements)
references
References 37 publications
(72 reference statements)
19
252
1
Order By: Relevance
“…Meyer et al (2005) were able to correlate the greater contribution of anammox to the production of N 2 with a greater availability of NO 2 -in the pore water. Together this corroborated a link between organic carbon and a supply of NO 2 -via NO 3 -reduction (Trimmer et al 2003. The importance of NO 3 -was confirmed by Risgaard-Petersen et al (2004), who found no significant anammox activity in Norsminde Fjord but an ra of up to 22% in Randers Fjord; in Rander Fjord, NO 3 -was abundant in the water column and penetrated into the sediment, but was absent in Norsminde Fjord.…”
Section: Open Pen Access Ccessmentioning
confidence: 58%
See 2 more Smart Citations
“…Meyer et al (2005) were able to correlate the greater contribution of anammox to the production of N 2 with a greater availability of NO 2 -in the pore water. Together this corroborated a link between organic carbon and a supply of NO 2 -via NO 3 -reduction (Trimmer et al 2003. The importance of NO 3 -was confirmed by Risgaard-Petersen et al (2004), who found no significant anammox activity in Norsminde Fjord but an ra of up to 22% in Randers Fjord; in Rander Fjord, NO 3 -was abundant in the water column and penetrated into the sediment, but was absent in Norsminde Fjord.…”
Section: Open Pen Access Ccessmentioning
confidence: 58%
“…Our findings provide firm evidence that the anammox reaction is widespread in estuarine sediments. Trimmer et al 2003), we showed a clear trend of increasing contribution of anammox to N 2 (ra, %) with increasing organic carbon and NO 3 -further upstream. This pattern was in stark contrast with that reported for the coastal sediments, but since then has also been reported for the subtropical Logan-Albert estuary system in Australia ) and for parts of Chesapeake Bay (Rich et al 2008).…”
Section: Open Pen Access Ccessmentioning
confidence: 66%
See 1 more Smart Citation
“…Subsequently, the vials were portioned into three treatments, which were spiked through the stopper of each vial with 100 μL of N 2 -purged stock solution of (1) . The rate and potential contribution to N 2 production of either anammox or denitrification were calculated as described before (Thamdrup and Dalsgaard 2002;Trimmer et al 2003).…”
Section: Anammox and Denitrification Activity Measurement With 15 N-lmentioning
confidence: 99%
“…In the meantime, many studies have shown that the anammox bacteria and the annamox process are ubiquitous and constitute a substantial sink of fixed nitrogen in the oceans (Dalsgaard et al, 2003;Kuypers et al, 2003;Penton et al, 2006;Schmid et al, 2007). The process is also significant in minimum oxygen zones (Kuypers et al, 2005;Hamersley et al, 2007;Jaeschke et al, 2007), sediments (Engstrom et al, 2005;Penton et al, 2006) and estuaries (Trimmer et al, 2003;Tal et al, 2005). These are all mesophilic to cold environments, and it is presently unknown whether anammox bacteria are also active at higher temperatures in marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%